Impacts of Africa RISING in Malawi - Haile, Beliyou; Azzarri, Carlo; Boukaka, Sedi Anne; Vitellozzi, Sveva; Chikowo, Regis (International Food Policy Research Institute, 2023)
This study evaluates the impact of Africa RISING, a large-scale sustainable intensification (SI) program that has been implemented in Central Malawi’s Dedza and Ntcheu districts beginning in 2012. Using a participatory action research framework, the program validated and promoted alternative SI options including fertilized maize, maize-legume intercropping, intercropping of two compatible legumes, cereal-legume rotation, and double-row planting of legumes. Impact is estimated on several SI indicators and domains using two rounds of panel data and difference-in-differences techniques. The unique study design allowed us to estimate impact by comparing outcomes among program beneficiaries with two different counterfactual groups—one located inside program villages (within village comparison) and another in non-program (control) villages (out-of-village comparison). We also conduct a placebo test comparing non-beneficiaries in the two counterfactual groups. The within-village comparison shows positive impact on several agricultural and economic indicators including access to agricultural information, value of harvest, on-farm diversity, labor productivity, annual net household income, per capita household consumption expenditure, household wealth, commercial orientation, and household dietary diversity score. We do not find a statistically significant impact on human indicators such as child and maternal nutrition. Estimates based on within-village, out-of-village, and placebo comparisons suggest important insights about the challenges in assessing the impact of agricultural programs in general and, specifically, participatory multi-intervention programs in the presence of sample (self-)selection and spillovers. Our study highlights important lessons learned to inform future program design and impact assessments.